Not just money: unequal responsiveness in egalitarian democracies. Issue 12 (2nd December 2021) - Elsässer, Lea; Hense, Svenja; Schäfer, Armin
ABSTRACT : A growing body of research has documented political inequality along class lines at different stages of the representation process. This article contributes to our understanding of unequal responsiveness and its causes with an in-depth study of Germany that investigates the link between preferences and policymakers' decisions. Using an original dataset covering 746 survey questions on specific reform proposals from 1980 to 2013, we provide the first study of a European democracy that investigates whether responsiveness patterns vary between economic and cultural policies or different governing coalitions. We show that decisions are skewed towards upper occupational and educational groups, irrespective of policy type or government composition. These results advance the discussion of potential mechanisms for unequal responsiveness. As privileged groups are overrepresented in parliament, our findings support the argument that the social bias in the make-up of parliaments matters for substantive representation.